Outside the Classroom and Beyond Psychology: A Citation Analysis of the Scientific Influence of Teaching Activities. (January 2015) - Tomcho, Thomas J.; Foels, Rob; Walter, Mark I.; Yerkes, Kyle; Brady, Brittany; Erdman, Molly; Dantoni, Lindsay; Venables, Megan; Manry, Allison
A primary objective for researchers who publish teaching activities and methods in the Teaching of Psychology (ToP) is to inform best practices in classroom teaching. Beyond the learning effect in the classroom, these ToP teaching activity and method articles may also have a scientific effect that heretofore researchers have overlooked. Therefore, we conducted a bibliometric examination of 765 teaching activities published in ToP from 1975 to 2007. Teaching activities are cited a surprisingly high number of times. More important, approximately half of the citations were from sources other than ToP, demonstrating a broader scientific influence. Further, we found that teaching research citation rates are comparable to authors' other peer-reviewed traditional psychology discipline research. We discuss findings in terms of implications for teaching as research, the potential effect of citations on tenure and promotion decisions, and ToP as a hub science.